Occupational therapy predischarge home visits for patients with a stroke (HOVIS): results of a feasibility randomized controlled trial. (May 2013) - Drummond, AER; Whitehead, P; Fellows, K; Sprigg, N; Sampson, CJ; Edwards, C; Lincoln, NB
Objective: To assess the feasibility of conducting a randomized controlled trial of occupational therapy predischarge home visits for people after stroke. Design: Randomized controlled trial and cohort study. We randomized eligible patients for whom there was clinical uncertainty about the need to conduct a home visit to a randomized controlled trial; patients for whom a visit was judged 'essential' were enrolled into a cohort study. Setting: Stroke rehabilitation unit of teaching hospital. Participants: One hundred and twenty-six participants hospitalized following recent stroke. Interventions: Predischarge home visit or structured, hospital-based interview. Main outcome measures: The primary objective was to collect information on the feasibility of a randomized controlled trial, including eligibility, control intervention and outcome assessments. The primary outcome measure was the Nottingham Extended Activities of Daily Living Scale at one month after discharge from hospital. Secondary outcomes included mood, quality of life and costs at one week and one month following discharge. Results: Ninety-three people were allocated to the randomized controlled trial; 47 were randomized to intervention and 46 to control. Thirty-three were enrolled into the cohort study. More people were allocated to the randomized controlled trial as the study progressed. One hundred and thirteen people (90%) received the proposed intervention, although there was a need for stricter protocol adherence. Follow-up was good: at one month 114 (90%) were assessed. There were no significant differences between the groups in the randomized controlled trial for the primary outcome measure at one month. The average cost of a home visit was £208. Conclusion: A trial is feasible and warranted given the resource implications of predischarge occupational therapy home visits.